Karakteristik Daerah Penangkapan Ikan Cakalang Pada Musim Barat di Perairan Teluk Bone - Jufri, Adi; Amran, M Anshar; Zainuddin, Mukti (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2014)
The purpose of this study was to characterize potential fishing ground for the skipjack tuna using the oceanographic conditions of sea surface temperature and chlorophyll-a concentrations and catch data, and to describe the level of primary productivity around the skipjack fishing grounds in the Bone Bay. This study used a survey method by collecting primary tuna catch and MODIS satellite image data. The data were analyzed using Empirical Cumulative Distribution Function (ECDF). The model outputs were visualized using ArcGIS spatial analyst. The results showed that the potential skipjack tuna fishing grounds during the west monsoon ( December -February ) were well characterized by the environmental conditions of SST and chlorophyll- a concentration ranged from 29.9 to 31.0 °C and from 0.12 to 0.22 mg m3, respectively. The highest catches for skipjack were found in February in the specific areas of 120°E121°E and 3°S-4°S where the levels of primary production ranged from 5.30 to 11.62 g C/m/ month during the west monsoon.